Evaluación de la aplicación de la teoría de restricciones (toc) en un proceso de elaboración de productos plásticos bajo pedido - Retamales García, María Laura (2010)
Plástica SA, has been for many years a make to order company of sleeves and rolls of plastic, known in the market for its high level of quality. Since its foundation, the company has worked under the same system control of production, which in recent years has shown weaknesses. As a result, the company has suffered a decline in sales levels, especially because of the delivery times offered which are above the times offered by its competitors. For this reason, the company wants to implement a control system that provides delivery times equal to those promised by the market, while complying with more than 99% of the dates offered to customers. To achieve the company's goal we implemented through a simulation model The Theory of Constraints (TOC) philosophy created by Dr. Eliyahu M. Goldratt in the early 80s. By implementing TOC tools such as: system control Simplified Drum-Buffer-Rope (SDBR) and buffer management in the simulated process, it was managed to deliver 100% of customer orders on time obtaining a marked decrease production times and a considerable reduction on work in process.